Contemporary patterns of presentation, diagnostics and management of upper tract urothelial cancer in 101 centres: the Clinical Research Office of the Endourological Society Global upper tract urothelial carcinoma registry - Baard, Joyce; Cormio, Luigi; Cavadas, Vitor; Alcaraz, Antonio; Shariat, Shahrokh F; de la Rosette, Jean; Laguna, Maria P (Current opinion in urology, 2021)
PURPOSE OF REVIEW: To assess patterns of presentation, diagnostics and treatment in patients with upper tract urothelial carcinoma (UTUC), a multicentre registry was launched. Clinical data of UTUC patients were prospectively collected over a 5-year period. RECENT FINDINGS: Data from 2380 patients were included from 2014 to 2019 (101 centres in 29 countries). Patients were predominantly male (70.5%) and 53.3% were past or present smokers. The majority of patients (58.1%) were evaluated because of symptoms, mainly macroscopic hematuria. Computed tomography (CT) was the most common performed imaging modality (90.5%). A ureteroscopy (URS) was part of the diagnostic process in 1184 (49.7%) patients and 488 (20.5%) patients were treated endoscopically. In total, 1430 patients (60.1%) were treated by a radical nephroureterectomy, 59% without a prior diagnostic URS. Eighty-two patients (3.4%) underwent a segmental resection, 19 patients (0.8%) were treated by a percutaneous tumour resection. SUMMARY: Our data is in line with the known epidemiologic characteristics of UTUC. CT imaging is the preferred imaging modality as also recommended by guidelines. Diagnostic URS gained a stronger position, however, in almost half of patients a definitive treatment decision was made without complete endoscopic information. Only one-third of patients with UTUC are currently treated with kidney sparing surgery.
Keywords: nádory ledvin; ureteroskopie; Registries; Female; nefroureterektomie; registrace; Ureteroscopy; Humans; ženské pohlaví; nádory močovodu; mužské pohlaví; Male; lidé; Ureteral Neoplasms; Kidney Neoplasms; Carcinoma, Transitional Cell; karcinom z přechodných buněk; Nephroureterectomy